Indocyanine green–assisted dental imaging in the first and second near‐infrared windows as compared with X‐ray imaging. Issue 1 (5th April 2019) - Li, Zhongqiang; Zaid, Waleed; Hartzler, Thomas; Ramos, Alexandra; Osborn, Michelle L.; Li, Yanping; Yao, Shaomian; Xu, Jian
Abstract: Indocyanine green (ICG) has been widely used in medical imaging, such as in retinal angiography. Here, we describe a pilot ex vivo study of ICG‐assisted near‐infrared fluorescence (NIRF) dental imaging in the first (700–950 nm for ICG‐NIRF‐I) and second (1000–1700 nm for ICG‐NIRF‐II) NIR windows using human extracted teeth; our study is compared with the traditional prevalent X‐ray imaging and NIR II illumination (NIRi‐II, 1310 nm) without ICG enhancement. The results show that ICG fluorescence has much better imaging contrast in both windows compared with NIRi‐II (by quantitatively comparing NIR intensity of the critical neighboring structures, such as enamel and dentin). Cracked teeth, notoriously hard to diagnose by dental X‐ray and computed tomography, were clearly profiled in NIRF dental imaging. An insidious occlusal caries, missing in X‐ray imaging, became a bright dot that was readily observed in ICG‐NIRF‐I images. For dental decay, NIRF imaging with ICG enhancement could clearly delineate the decay boundary. NIRF in both windows distinguished interproximal and occlusal superficial caries. Overall, ICG‐assisted NIRF dental imaging has unique advantages in identifying cracked teeth and insidious caries. The two NIR imaging windows used in our study might one day serve as noninvasive and nonionizing‐radiation methods for the diagnosis of critical dental diseases in situ . Abstract : In the present study, we explore the feasibility of indocyanine green–assisted dental imaging in near infrared (NIR) I and II windows on extracted human teeth, compared with traditional NIR dental illumination (∼1, 310 nm) and prevalent dental X‐ray–based imaging.